2011
DOI: 10.1609/aimag.v32i4.2377
|View full text |Cite
|
Sign up to set email alerts
|

How People Talk with Robots: Designing Dialogue to Reduce User Uncertainty

Abstract: If human-robot interaction is mainly shaped by users’ strategies to deal with their unfamiliar artificial com¬munication partner, as it is suggested here, robot dialog design should orient at reducing users’ uncertainty about the affordances of the robot and the joint task. Two experiments are presented that investigate the impact of verbal robot utterances on users’ behavior; results show that users react sensitively to subtle linguistic cues that may guide them into appropriate understandings of the robot. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…In a follow-up study, we utilised robots with strikingly different embodiments in the same scenario with the same behaviour set borrowed from hearing dogs. We showed that the appearance of the robot has only minor effect on how humans recognize the goal directed behaviour ('intent') of these robots , supporting earlier results found by Fischer (2011).…”
Section: The Problem Of Resemblancesupporting
confidence: 89%
“…In a follow-up study, we utilised robots with strikingly different embodiments in the same scenario with the same behaviour set borrowed from hearing dogs. We showed that the appearance of the robot has only minor effect on how humans recognize the goal directed behaviour ('intent') of these robots , supporting earlier results found by Fischer (2011).…”
Section: The Problem Of Resemblancesupporting
confidence: 89%
“…The design choices for the dialog interface of our PbD system are influenced by work on spoken interactions with robots within the human-robot interaction (HRI) literature [7,8,21]. Work in the field of human-computer interaction which investigate how the system feedback influences human input [9,16,6] also have implications for human-robot dialog, and have been considered in the design of our system.…”
Section: Related Workmentioning
confidence: 99%
“…Extrapolating from previous work in human–computer interaction suggests that people may involuntarily and automatically interact with robots like they interact with humans (Reeves & Nass, ). Instead, comparisons between child‐directed and robot‐directed speech in this project revealed interaction to be mainly based on participants' perceptions of the robot's affordances (Fischer, ). Users' preconceptions also influence their interactions with robots considerably, guiding them to a particular understanding of the situation (Fischer, ).…”
Section: How Humans Talk To Robots (And Why)mentioning
confidence: 96%